Stock exchanges. - Rodrigues Da Costa, J. (2019)
Merging Stock and Derivative Exchanges seems to be unavoidable-even across national borders-since the extraordinary development of telecommunication and computer technologies has made both of them the efficient and inexpensive constituents of any proposal for a centralized market. However, Exchanges are not exactly equal to any other commercial enterprise and, in particular, they are not yet separable from the sovereign vectors that were traditionally connected to them. In the future things may be different, but we cannot forget that the world is still made up of independent countries. This makes a multinational company of Exchanges a new type of conglomerate that has no historical reference to guide us. The model of a multinational corporation expanding from the mother country to overseas markets seems not to be quite the right approach. Additionally, different countries are in different stages of their development and evolution, and financial maturity is an area of vast differences among nations. Therefore, the central management team of this particular multinational firm cannot organize and run the company in exactly the same way as any other global company. If the whole group does not exist to meet all the details of each individual national market, the small and undeveloped markets will not be able to participate in this consolidation movement. Those countries that have entered the NYSE Euronext group are a vivid proof of the inconveniences of such participation. The experience of NYSE Euronext deserves the attention of scholars, as this is the vanguard case of an undertaking of this nature.